(untitled) (Revue El-Wahat pour les Recherches et les Etudes, 2021)
The Algerian History Is Full Of Recordings Of Multiple Contributions Made By Southern Algeria Scholars. Firstly, They Had Been Holding Islamic Judiciary Positions During The French Colonization Era. Secondly, They Served In The Algerian Justice Sector In Post-Independence Era. Thirdly, Their Contributed Invaluably To The Legislation Movement In Independent Algeria. Cheikh Amhemed Bin Sulaeiman Metheri, Being One Of The Southern Algeria Scholars, Has Prominently Contributed To Fields Of Law Development; Therefore, He Is Taken As A Sample In This Study. The Biography Of Cheikh Metheri Showcases The Importance Of His Contributions To The Development Of Fields Of Law Through His Roles In Justice, Legislation, And Fiqh. Key Words- Field Of Law,Justice,Legislation,Fiqh,Branches Of Law,Court Hierarchy,Bill Of The Algerian Family Law.